PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN LAKU PANDAI AGEN46 KABUPATEN BANDUNG - Klacia Rizky Pratama; Tri Widarmanti (ITB AAS Indonesia Surakarta, 2024)
BNI has various types of services that are tailored to customer needs, such as the creation of a BNI branchless banking called Agen46. Agent46 partners are usually found in grocery stores, retail outlets, and others that are easy for the public to find. Branchless banking is also known as Laku Pandai. This type of banking uses digital and mobile technologies to provide financial services to customers, enabling them to make transactions without visiting a physical bank location. The purpose of this study was to determine the effect of service quality on customer loyalty, to determine the effect of service quality on customer loyalty, to determine the effect of customer satisfaction on customer loyalty, and to determine customer satisfaction as a mediator of the relationship between service quality and customer loyalty. This study uses a quantitative method with probability sampling and has carried out tests including validity, reliability, testing by distributing 100 questionnaires to the people of Bandung Regency and data obtained with the IBM SPSS 26 tool. The results show that customer satisfaction is a strong intervening variable to mediate the effect of service quality on customer loyalty because all the variables in the study have significant influence.